Factors influence employee engagement among employees at Lembaga Kemajuan Wilayah & Luar Bandar (KEDA) / Naziha Syazliana Othman and Mira Qerul Barriah Muhamad - Othman, Naziha Syazliana; Muhamad, Mira Qerul Barriah (Faculty of Business and Management, 2015)
This research was conducted to carry out a study entitled “Factors Influence Employee Engagement among Employees at Lembaga Kemajuan Wilayah & Luar Bandar (KEDA)”. The purpose is actually to study on the relationship between three independent variables against one dependent variable. Basically, it consists of three factors influencing employee engagement among employees and the factors include working hours, internal communication and employee commitment. The study reported is based on the questionnaire circulated to employees in Lembaga Kemajuan Wilayah & Luar Bandar Negeri Kedah. Plus, this study could make important contribution to extent research in management and organizational behavior. In order to complete this thesis, a few hypotheses were constructed and focused on the objectives to determine whether there were significant relationships between the variables. For this study, 100 employees working in Lembaga Kemajuan Wilayah & Luar Bandar Negeri Kedah were chosen as respondents. The data was obtained from primary data by using questionnaire. All data collected through questionnaire were analysed systematically by using Statistical Package for Social Science (SPSS).